تأثير مواعيد إضافة السماد البوتاسي والكثافة النباتية في المسطح الورقي والمحصول البيولوجي والإنتاجية لنبات الفول السوداني - عبد العزيز محمد; سليمان علي; صارم سناء (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث خلال الموسمين الزراعيين 2008 ـ 2009 في منطقة عرب الملك, لدراسة تأثير أربعة مواعيد لإضافة السماد البوتاس هي: 1 ـ شاهد (إضافة عند الحراثة الخريفية). 2 ـ إضافة قبل الزراعة بشهر. 3 ـ إضافة عند الزراعة. 4 ـ إضافة 50% قبل الزراعة بشهر و50% عند التفريع، وثلاث كثافات هي 6.7، و8.3 و11.1نبات/م2، والتفاعل بين هذين العاملين على المسطح الورقي والمحصول البيولوجي والإنتاجية لنبات الفول السوداني. أظهرت الدراسة النتائج الآتية: تفوق موعد إضافة السماد البوتاسي قبل الزراعة بشهر على الشاهد وعلى جميع مواعيد الإضافة المدروسة في المسطح الورقي (بعد 50 و80 و110 أيام من الزراعة) وفي المحصول البيولوجي غ/نبات، وإنتاجية القرون كغ/هـ خلال موسمي البحث. تفوق موعد إضافة 50% من السماد البوتاسي قبل الزراعة بشهر واحد في وزن القرون الجافة غ/نبات. تفوقت الكثافة النباتية 6.7 نبات/م2 في مساحة المسطح الورقي والمحصول البيولوجي ودليل البذار، وإنتاجية النبات من القرون الجافة على الكثافتين 8.3 و11.1 نبات/م2 بينما تفوقت الكثافة 11.1 نبات/م2 على الكثافتين 8.3 و 6.7 نبات/م2 في إنتاجية الهكتار من القرون الجافة. أعطى التفاعل بين موعد الإضافة قبل الزراعة بشهر والكثافة 11.1 نبات/م أفضل إنتاجية من القرون الجافة قدرت وسطياً 3952.4 كغ/هـ في الموسم الأول و4184.3 كغ/هـ في الموسم الثاني. This research has been carried out during 2008 and 2009 in Arab Elmolk area, in order to study the effect of four different dates of adding potassium fertilizer. The first (control) is adding at Autumn plowing; the second adding is one month before seedling; the third adding is at seedling; and the fourth adding is 50% one month before seedling, and 50% per branching, and 3 plants densities: 6.7, 8.3 and 11.1 plant/m2, and the interaction between these two factors on leaf area, biological crop and yield of peanut plant. The results of this research are the following: The adding of fertilizer one month before seedling showed an increase on control and all other adding dates in leaf area (after, 50- 80- 110 days), and biological yield g/plant, and yield pods kg/ha. during of the two seasons. Adding 50% one month before seedling showed an increase in weight of dry pods g/plant. The planting density 6.7 plant/m2 showed an increase of leaf area, and biological/plant and plant dry yield/pods and index seeds on the two densities 8.3 and 11.1 plant/m2, while increasing density 11.1 plsnt/m2 on the other plants density of yield dry pods/haَ. The interaction between adding date one month before seedling and plant density 11.1 plant/m2 gave better yield from dry pods average 3952.4 kg/haَ and 4184.3 kg/haَ during the first and second seasons.